Media Repertoires of Japanese Old Users in the Digital Media Environment - Tomoko Takemura (International Telecommunications Society (ITS), 2019)
The purpose of this study is to explore media repertoires emerging from Japanese old media users and factors which can explain the use of different media repertoires to understand a new digital divide called "gray divide," the inequality in the access to and use of ICT within senior citizen sector. Data of this study was based on the Public Opinion survey "The Japanese and Television 2015" conducted by NHK Broadcasting Culture Research Institute. Gender, education, and age were the most powerful predictors of media use repertoires. This finding advances our understanding of the relationship between media use repertoires and influential factors.
Keywords: 330